Simplified method of estimating electric field above the finitely conductive earth surface due to a generalised source in air - 409290 Md. Mortaza Ali; Hussein Ahmad, 1953-; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Elektrik
15